Examining the Influence of Tutors on Learning Management System Use in Driving Motivation and Effectiveness of Online Learning - Wildoms Sahusilawane; Lilian Sarah Hiariey; Mouren Wuarlela (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examines the role of tutor facilitation in optimizing the use of the Learning Management System (LMS) to enhance learning motivation and online learning effectiveness among millennial students. Although LMS platforms are widely implemented, prior research has focused on technological aspects, leaving the pedagogical role of tutors as mediators of LMS-based learning outcomes underexplored. A quantitative design involved 160 students from Universitas Terbuka in Indonesia. Data were collected via structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results indicate tutor facilitation contributes significantly to students' learning motivation and the effectiveness of LMS-based online learning. The structural model demonstrates explanatory power and predictive relevance, confirming the tutor's key role in strengthening the link between technology adoption and student learning outcomes. Practical implications include strengthening tutors' pedagogical and digital competencies and recommending institutional policies that integrate technological support with human facilitation to improve learning. Further research should employ cross-institutional samples and mixed-method approaches to enhance generalizability.